Learning from the challenges of undertaking an evaluation of a multi-partner housing support initiative delivered within a hospital setting - A. Foster; E. Holding; E. Lumley; S. Roxby; D. Portman; J. Holliday; A. Peace; I. Del Rosario; W. Khan; A. Brenman; M. Gillett; E. Goyder (Elsevier, 2022)
Objectives: We present learning from a mixed-methods evaluation of a housing support initiative for hospital inpatients. Study design: A mixed-methods process evaluation. Methods: A social housing provider delivered a housing support service in two hospitals (mental health unit and general hospital). Healthcare providers, the social housing provider and academic researchers designed and undertook a co-produced, mixed-methods process evaluation of the intervention. The evaluation included questionnaires, semi-structured interviews, analysis of routinely collected data and economic analysis. Despite commitment from the partners, the evaluation faced challenges. We reflect on the lessons learnt within our discussion paper. Results: Despite the commitment of the partners, we faced several challenges.We took an iterative approach to the design and processes of the evaluation to respond to arising challenges. Recruitment of service-users was more difficult than anticipated, requiring additional staff resources. Given the small-scale nature of the intervention, and the quality of data recorded in hospital records, the planned economic analysis was not feasible. Positive factors facilitating evaluation included involvement of staff delivering the intervention, as well as managers. Being able to offer payment to partner organisations for staff time also facilitated ongoing engagement. Conclusions: Multi-partner evaluations are useful, however, researchers and partners need to be prepared to take an iterative, resource intensive approach. Both availability and quality of routine data, and the resources required to support data collection, may limit feasibility of specific methods when evaluating small-scale cross-sector initiatives. Thus, this necessitates a flexible approach to design and analysis.